Peningkatan Kapasitas Aparat Pemerintah Desa Menuju Desa Adaptif Iklim di Kecamatan Segedong, Kabupaten Mempawah - Masykur Amin; Hendayana; Dwi Agus Sumarno (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2025)
Climate change generates various hydrometeorological risks in coastal and wetland areas, including Segedong District, Mempawah Regency, which affect the agriculture and fisheries sectors. This issue has not been fully integrated into village planning and budgeting, making the strengthening of village government officials’ capacity a key factor in realizing climate-adaptive villages. This community service program aims to enhance the capacity of village government officials in understanding climate change, mitigation, adaptation, and climate-adaptive village planning, as well as to examine the effectiveness of the capacity-building program. The program was implemented using a one-group pre-test–post-test design through a series of lectures, interactive discussions, and group work involving village heads, village secretaries, and other village officials from several villages in Segedong District. Quantitative data from the pre-test and post-test were analyzed descriptively to measure changes in knowledge, while qualitative data from discussions and group presentations were analyzed thematically to identify changes in understanding and planned actions. The results show a significant increase in knowledge, with the average score rising from 47% (pre-test) to 86% (post-test). Participants were also able to identify key climate risks in their respective villages and formulate initial adaptation measures, such as adjusting planting calendars, improving drainage, planting protective vegetation, and integrating climate issues into village development planning meetings. This community service activity concludes that a structured capacity-building program is effective in strengthening local readiness toward climate-adaptive villages and should be followed up with assistance in the preparation of village planning documents.